The role of the TAPSE/sPAP ratio as a predictor of mortality in Pulmonary Arterial Hypertension: Its value for patient risk stratification - Paul Palacios-Moguel, MD; Guillermo Cueto-Robledo, MD; Héctor González-Pacheco, MD; Jorge Ortega-Hernández, MD; María Berenice Torres-Rojas, MD; Dulce Iliana Navarro-Vergara, MD; Marisol García-Cesar, MD; Cinthia Alejandra González-Nájera, MD; Carlos Alfredo Narváez-Oríani, MD; Julio Sandoval, MD (JHLT Open)
Background: The tricuspid annular plane systolic excursion and systolic pulmonary artery pressure (TAPSE/sPAP) ratio has been proposed as an indicator of ventriculo-arterial coupling, predicting right ventricular failure (RVF) and mortality in patients with pulmonary arterial hypertension (PAH). Objective: To evaluate the usefulness of the TAPSE/sPAP ratio in predicting outcomes and improving risk stratification in patients with PAH. Methods: 156 patients with PAH were included. Clinical, functional, echocardiographic, and haemodynamic variables, along with the TAPSE/sPAP ratio, were analysed based on etiological PAH subgroups and outcomes. Additional statistical measures, such as the area under the curve (AUC), net reclassification index (NRI), and integrated discrimination improvement, assessed the predictive ability of TAPSE/sPAP in combination with the ESC/ERS risk score, and other risk assessment strategies (COMPERA and Reveal Lite 2). Results: Most patients were female (86.5%), with a median age of 45.5 (IQR: 29–58) years. The TAPSE/sPAP ratio for the whole group was 0.26 (IQR: 0.190–0.347) mm/mmHg, which was similar among different aetiologies, but different between deceased and surviving patients (0.14 vs. 0.27 mm/mmHg, respectively, P < 0.001). A TAPSE/sPAP ratio <0.18 mm/mmHg independently predicted mortality (AUC: 0.859, 95% CI: 0.766– 0.952; P < 0.001). Integration with the ESC/ERS risk score improved predicted mortality (AUC: 0.87 vs. 0.75, p = 0.002) and risk stratification, reclassifying 14.28% of events and 36.92% of non-events, with an NRI of 39.4% (P < 0.001). Likewise, integration with other scores improved predicted ability of COMPERA and REVEA Lite2; COMPERA+TAPSE/sPAP (AUC: 0.837 vs 0.742; p = 0.005) and REVEAL Lite 2 +TAPSE/sPAP (AUC: 0.840 vs. 0.713; p < 0.001). Conclusions: A TAPSE/sPAP ratio <0.18 mm/mmHg predicts mortality in PAH. The combination of the TAPSE/sPAP ratio with the ESC/ERS risk score improved risk stratification, and reclassification emphasizing the potential of ESC/ERS+TAPSE/sPAP as a valuable tool for risk assessment and clinical decision-making in PAH patients. Integration of TAPSE/sPAP ratio with other scores (COMPERA and (REVEAL Lite 2) also improved the risk stratification and reclassification of these risk scores.